Dampak Kecerdasan Emosional, Budaya Organisasi dan Gaya Kepemimpinan terhadap Organizational Citizenship Behavior pada Pegawai - Febyola Puspa Dewani; Agus Suyatno; Esti Dwi Rahmawati (Institut Nalanda, 2024)
The purpose of this study is to analyze the influence of Emotional Intelligence, Organizational Culture and Leadership Style on Organizational Behavior in Employees of Grand Laguna Hotel and Villa Karanganyar.The approach used in this study uses Multiple Linear Regression analysis technique with the population of all employees of Grand Laguna Hotel and Villa Karanganyar The sample of this study is 50 respondents who work at Grand Laguna Hotel and Villa Karanganyar.Technique Data collection in this study used a questionnaire and was processed using IBM SPSS Statistic 25. The conclusion of the results of this study is that there is an influence of the three independent variables on the dependent variables studied in this study. Emotional Intelligence, Organizational Culture, and Leadership Style have a positive and significant effect on Organizational Citizenship Behavior.